Generation of a gene-corrected human induced pluripotent stem cell line derived from a patient with laterality defects and congenital heart anomalies with a c.455G > A alteration in DAND5. - Inácio, José M. (2020)
This work was supported by Fundação para a Ciência e a Tecnologia (PTDC/ BIM-MED/3363/2014) and iNOVA4Health -UID/Multi/04462/ 2013, a program financially supported by Fundação para a Ciência e Tecnologia/ Ministério da Educação e Ciência, through national funds and co-funded by FEDER under the PT2020 Partnership Agreement.